A population‐based study of the incidence of delusional infestation in Olmsted County, Minnesota, 1976–2010. (1st May 2014) - Bailey, C.H.; Andersen, L.K.; Lowe, G.C.; Pittelkow, M.R.; Bostwick, J.M.; Davis, M.D.P.
Summary: Background: Delusional infestation (DI) is a well‐recognized clinical entity but there is a paucity of reliable data concerning its epidemiology. Knowledge of the epidemiology is fundamental to an understanding of any disease and its implications. Epidemiology is most accurately assessed using population‐based studies, which are most generalizable to the wider population in the U.S. and worldwide. To our knowledge, no population‐based study of the epidemiology (particularly incidence) of DI has been reported to date. Objectives: To determine the incidence of delusional infestation (DI) using a population‐based study. Methods: Medical records of Olmsted County residents were reviewed using the resources of the Rochester Epidemiology Project to confirm the patient's status as a true incident case of DI and to gather demographic information. Patients with a first‐time diagnosis of DI or synonymous conditions between 1 January 1976 and 31 December 2010 were considered incident cases. Results: Of 470 identified possible diagnoses, 64 were true incident cases of DI in this population‐based study. The age‐ and sex‐adjusted incidence was 1·9 [95% confidence interval (CI) 1·5–2·4] per 100 000 person‐years. Mean age at diagnosis was 61·4 years (range 9–92 years). The incidence of DI increased over the four decades from 1·6 (95% CI 0·6–2·6) per 100 000 person‐years in 1976–1985 to 2·6 (95% CI 1·4–3·8) per 100 000 person‐years in 2006–2010. Conclusions: Our data indicate that DI is a rare disease, with incidence increasing across the life span, especially after the age of 40 years.